Exposure to a mycovirus containing Aspergillus Flavus reproduces acute lymphoblastic leukemia cell surface and genetic markers in cells from patients in remission and not controls. (2021) - Tebbi, Cameron K.; Badiga, Aruna; Sahakian, Eva; Powers, John J.; Achille, Alex N.; Patel, Saumil; Migone, Felicia
Highlights: A mycovirus containing Aspergillus Flavus (MCAF) was cultured from the home of a patient with acute lymphoblastic leukemia (ALL). Culture was evaluated by electron microscopy, protein analysis and mass spectrometry which revealed that it contains a mycovirus and lacks any aflatoxin production. Exposure to the supernatant of the culture of MCAF reproduced ALL genetic and surface markers in the peripheral blood mononuclear cells from ALL patients in complete remission and not controls. These studies are unprecedented and provides new information and avenues in the investigation of leukemogenesis in ALL. Abstract: The etiology of acute lymphoblastic leukemia (ALL) remains unknown. A recent "two-hit" model for the occurrence of precursor B cell acute lymphoblastic leukemia propose that this disease arises through a two-step process, including predisposing genetic mutation and exposure to infections. While several genetic mutations are proposed, no infection category has been suggested. We have isolated a certain Aspergillus Flavus from residence of an ALL patient. This organism contains mycovirus and does not produce aflatoxin. The supernatant of culture of this mycovirus containing Aspergillus Flavus (SAF) was tested on the PBMCs of ALL patients in remission and controls. Cell surface phenotypes and genetic markers were examined. The effects of its combination with Epstein-Barr virus (EBV) was also investigated. For the SAF, positive and negative controls were aflatoxin and culture of Mycocladus corymbifer, respectively. Controls for ALL were sickle cell patients undergoing exchange transfusion. Incubation of the PMBCs from ALL patients in remission, or controls, with SAF resulted in re-development of ALL cell surface phenotypes and genetic markers in ALL patients in remission and not controls. These differentiating effects were not seen with aflatoxin or culture of Mycocladus Corymbifer . Addition of EBV did not alter effects of SAF. Currently, there are no techniques to discriminately reproduce characteristic leukemic genetic markers and cell surface phenotypes in cells from ALL patients in remission and not controls. These studies may provide a test for recognition of ALL patients in remission and new prospects for the investigation of leukemogenesis.